The use of documentary archive for make visible the participation of women in the teaching of Mexican History - Juárez Pérez, Angélica Noemí (Clio. History and History Teaching, 2019)
Different historiographical currents have founded its research on social actors that in past times were not considered as social subjects. Such is the case of women. Nonetheless, this historiographical advance has not been reflected on school’s History curricula. This essay’s first part focuses on the absense of women as a historical subject in the junior highschool Mexican History curse. The second part addresses how documentary archives can become a resource to make women’s participation visible. Finally a didactic experience used at a highschool group in Mexico City is presented.
Keywords: History teaching; History instruction; historical sources; teaching proposal; secondary education